PLASTIC OF KEELED CHEST IN CHILDREN USING TITANIUM NICKELIDE MATERIALS - Слизовский, Григорий Владимирович; Титов, Михаил Владиславович; Кужеливский, Иван Иванович; Шикунова, Яна Владимировна; Ситко, Леонид Александрович; Сигарева, Юлия Андреевна (Mother and Baby in Kuzbass, 2018)
The article reflects principles of surgical treatment of keeled chest in the Tomsk Region. It describes an operative approach depending on the deformity kind. The work provides analysis of surgical treatment of 38 patients.There were presented main stages of new technique, which supplement the authors method of surgical intervention. It was noted that using titanium nickelide plates with the shape memory to correct keeled chest in children and adolescents is the method of choice and brings good clinical results.
Keywords: thorax surgery; keeled chest; thoracoplastic; titanium nickelid